Effect of Self-Management Technique on Aggressive Behaviour Tendency of Secondary School Adolescents in Enugu North Local Government Area (Journal of Guidance and Counselling Studies, 2023)
One of the major problems associated with adolescents in secondary schools today is the tendency to act aggressively towards their teachers, schoolmates, and others in the school. Such an aggressive tendency could bring about tension both in school and at home. This study investigated the effect of self-management techniques on the tendency to aggressive behaviour among secondary school adolescents in Enugu North Local Government Area, Enugu State. Two research questions guided the study, while two null hypotheses were tested at the 0.05 level of significance. The design for the study was quasi-experimental, non-randomised pre- and post-test, control group research. The sample consisted of 28 senior secondary school adolescents purposefully drawn from a population of 212 students. A standardised instrument, "Tendency to Aggressive Behaviour Questionnaire (TABQ)," was adapted and used for data collection. The internal consistency reliability coefficient for the instrument was 0.89. Data was collected through direct delivery of the instrument to the respondents. Mean scores were used to answer the research questions, while the null hypotheses were tested using Analysis of Co-variance (ANCOVA). The norm of the instrument (70.00) guided the decision. The findings of the study revealed, among others, that self-management techniques were significantly effective in reducing aggressive tendencies among adolescents. The findings further revealed that self-management techniques were more effective in reducing female secondary school adolescents’ aggressive tendencies. Based on the findings of the study, it was recommended that self-management techniques be adopted by counsellors in schools and other allied professionals as effective treatment techniques for reducing aggressive behaviour tendencies among secondary school adolescents.
Keywords: Self-management; technique; aggressive behaviour; tendency; school adolescents